Natural Resource Rents and Carbon Intensity Nexus in Saudi Arabia: Disaggregated Analyses - Mahmood, Haider (International Journal of Energy Economics and Policy, 2025)
Natural Resource Rents (NRR) can shape carbon emissions and Carbon Intensity (CI) in a resource-rich economy. However, NRR from each natural resource does not necessarily have the same effect on CI. Thus, this research aims to estimate the effects of oil, natural gas, mineral, and forest rents on CI in the resource-rich economy of Saudi Arabia by using the cointegration technique for a period of 1980-2023. The findings reveal that economic growth increases CI. Moreover, oil and natural gas rents exert a positive long-run effect on CI. However, mineral and forest rents could not affect CI in the long run. Furthermore, NRR from all investigated sources increases CI in the short run. These results emphasize the need for targeted policy measures for each source of NRR to reduce their environmental concerns. For this purpose, it is advised to diversify the Saudi economy from NRR.